Hubungan antara Dukungan Orang Tua dengan Motivasi Belajar Siswa Kelas Tinggi - Adnan K Adnan K; Ade Irma Agustriani; Muh. Idris Jafar (Jurnal Pendidikan dan Pembelajaran Sekolah Dasar (JPPSD), 2022)
The problem in this study is the lack of parental support for children, so students lack motivation in learning. This research is a quantitative research with correlational type which aims to determine whether there is a significant relationship between parental support and student motivation. The sampling technique used is non-probability sampling technique. The results showed that parental support was in the very good category with a percentage of 87.52% and students' learning motivation was in the very good category with a percentage of 91.35%. The tcount (8,1307) is greater (>) the ttable value (1,98896) which means H0 is rejected and H1 is accepted. Thus, it can be concluded that there is a significant relationship between parental support and student motivation at SDN 17 Bila, Lalabata District, Soppeng Regency. The higher the parental support, the higher the student's learning motivation.